Extent of prior lung irradiation and mortality in COVID-19 patients with a cancer history (2020)
Purpose: There have been nearly 200,000 deaths worldwide so far from coronavirus disease 2019 (COVID-19), which is caused by a coronavirus called SARS-CoV-2. Cancer history appears to be a poor prognostic factor for COVID-19 patients, although the reasons for this are unclear. In this report, we assess whether extent of prior lung irradiation is a risk factor for death as a result of COVID-19 infection. Methods and Materials: Patients who tested positive for COVID-19 between March 14 and April 15, 2020, at our institution and who previously received radiation therapy for cancer in our department were included in this analysis. Patient characteristics and metrics describing the extent of lung irradiation were tabulated. Cox regression models were used to identify predictors of death after COVID19 diagnosis. A logistic model was used to characterize the association between mean lung radiation therapy dose and 14-day mortality risk after COVID-19 diagnosis. Results: For the study, 107 patients met the inclusion criteria. With a median follow-up of 7 days from COVID-19 diagnosis for surviving patients, 24 deaths have been observed. The actuarial survival rate 14 days after COVID-19 testing is 66%. Increasing mean lung dose (hazard ratio [HR] per Gy Z 1.1, P Z .002), lung cancer diagnosis (HR Z 3.0, P Z .034), and receiving radiation therapy between 1 month and 1 year before COVID-19 testing (HR Z 3.4, P Z .013) were associated with increased risk of death. Our survival model demonstrates a near linear relationship between mortality risk after COVID-19 diagnosis and mean lung radiation therapy dose. Conclusions: COVID-19 patients with a history of radiation therapy for cancer have a poor prognosis, and mortality risk appears to be associated with extent of lung irradiation. Validation of these findings will be critical as the COVID-19 pandemic continues.